QUALITY PARAMETERS IN CONSERVATION-RESTORATION CHOICES – THE CASE OF THE TOWER OF THE WINDS IN ATHENS - Papadopoulou, Maria; Gazi, Andromache (Protection of Cultural Heritage, 2019)
The chemistry- and physics-based approach of conservation has led to the view that conservator-restorers use quantitative criteria which provide objective choices. Today, however, there is a shift of focus from material-centred to people-oriented approaches within the field of heritage preservation. This shift leads to a redefinition of the conservation-restoration field and its ethics in relation to society and calls for the adoption of diverse methodologies. Within this context, this paper discusses the qualitative factors which inform decision-making processes in conservation-restoration practice. More specifically, the paper examines the case of the so called “Tower of the Winds” in Athens and looks at the quality parameters which informed conservation-restoration work carried out at the Tower during 2014-2015. Overall, it is shown that the prominence of the quality parameters which inform contemporary conservation-restoration practice reveals the subjective dimension of conservation-restoration choices. The research has also showed that current trends tend to emphasize the historical rather than the aesthetic or other values of monuments.